2022
DOI: 10.1155/2022/4957996
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Circadian Clock Genes Associated with Tumor Immunity and Prognosis in Patients with Colon Cancer

Abstract: Early research shows that disrupting the circadian rhythm increases the risk of various cancers. However, the roles of circadian clock genes in colorectal cancer, which is becoming more common and lethal in China, remained to be unclear. In conclusion, the present study has demonstrated that multiple CCGs were dysregulated and frequently mutated in CRC samples by analyzing the TCGA database. The higher expression levels of REV1, ADCYAP1, CSNK1D, NR1D1, CSNK1E, and CRY2 had a strong link with shorter DFS time i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…This downregulated expression is prevalent in advanced stages of the disease and correlates with invasive carcinoma in cervical cancer [83]. In contrast, elevated ADCYAP1 mRNA levels are linked to a shorter disease-free survival time in colorectal cancer patients [84].…”
Section: Resultsmentioning
confidence: 99%
“…This downregulated expression is prevalent in advanced stages of the disease and correlates with invasive carcinoma in cervical cancer [83]. In contrast, elevated ADCYAP1 mRNA levels are linked to a shorter disease-free survival time in colorectal cancer patients [84].…”
Section: Resultsmentioning
confidence: 99%
“…Further studies have revealed differences in clock gene expression in cancerous tissues compared to healthy tissues. Meanwhile, a number of CCRGs-derived prognostic signature was developed to be effectively used in the prognosis prediction of various cancers, such as colon cancer, [19][20][21] The crucial molecular markers connected to CCRGs in BC, however, have not yet been adequately analyzed.…”
Section: Discussionmentioning
confidence: 99%